6.2k views
3 votes
Find general solution y=y(x) of the followig homogenous differential quations

1 Answer

4 votes

Final Answer:

The general solution to the homogeneous differential equation
\((dy)/(dx) - 2y = 0\) is given by
\(y(x) = Ce^(2x)\), where (C) is an arbitrary constant.

Step-by-step explanation:

The given differential equation is a first-order linear homogeneous differential equation. To find the general solution, we can rewrite it in standard form:
\((dy)/(dx) - 2y = 0\). The solution to this type of differential equation is commonly expressed in the form (y(x) = Ce
^(kx)\), where (C) is a constant and (k) is the coefficient of (x). In this case, (k = 2), so the general solution is
\(y(x) = Ce^(2x)\).

In the solution, the constant (C) represents the arbitrary constant of integration. This constant is determined by any initial conditions provided or through further information about the problem. The exponential term
\(e^(2x)\) arises from the fact that the differential equation is linear with a constant coefficient. The solution
\(y(x) = Ce^(2x)\) represents a family of functions that satisfies the given differential equation.

In summary, the general solution to the homogeneous differential equation
\((dy)/(dx) - 2y = 0\) is \(y(x) = Ce^(2x)\), where \(C\)is an arbitrary constant that can be determined based on specific initial conditions or additional information about the problem.

Full Question:

Find the general solution (y=y(x)) of the following homogeneous differential equation:


\[ (dy)/(dx) - 2y = 0 \]

User Fabe
by
7.7k points